Relações entre tecnologia e sustentabilidade da produção de milho em Sergipe a partir de indicadores biológicos da qualidade do solo - Oliveira, Osmundo Soares de (2011)
This research had two objectives. The first was to characterize the current process of modernization of the corn agribusiness in the Agreste and Center-South regions of Sergipe. Based on the intensification of financial capital and agricultural technology, it was observed that this process demonstrates the same elements that characterize the so-called ´conservative modernization´of agribusiness. These two elements, capital and intensive technology based on the uniform culture of crops, have redesigned the face of agriculture in that area of the State, which until recently was characterized by the use of traditional agricultural methods utilizing low-intensive technology and with low yields per unit area. Such changes in standard technology affect not only the economic sphere, which shows the most visible and immediate impacts, but also have significant social and, especially, environmental consequences. The environmental implications of agricultural modernization are the focus of the second objective of this research: to identify if those changes are impacting on the sustainability and soil quality of the region. This objective was addressed through an analysis of eight microbiological indicators of soil quality related to microbial biomass and enzymatic activities: microbial biomass carbon (MBC), microbial biomass nitrogen (MBN), total enzymatic activity (ETA), specific enzyme activities of acid phosphatase (ACP), -glucosidase (GLU) and urease (URA), basal soil respiration (BSR) and the metabolic quotient (qCO2). Five areas were chosen as treatments. Three of them involved the cultivation of maize (Zea mays L.): a) maize intercropped with beans (Phaseolus vulgaris L.) in conventional cultivation used by a typical family farm; b) conventional farming maize, but with the use of intensive technology, and; c) maize in a minimal system of cultivation, also using intensive technology. The final two treatments were represented by a pasture of Guinea grass (Panicum maximum Jacq. cv. Tanzania) associated with mesquite (Prosopis juliflora (Sw.) DC) and a control area of the transitional vegetation of the Caatinga. The results of three indicators: ETA, URA and MBN showed a tendency of increase in the soil quality when it was grown in a minimal system of cultivation. The ACP and GLU indicators showed deterioration in soil quality in every area of maize grown when compared to the native area and pasture, as for the MBC, BSR and qCO2 indicators there were no statistically significant changes in soil quality among the treatments.